2014
DOI: 10.1111/dme.12474
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial impact associated with diabetes‐related amputation

Abstract: The present study found that the impact of diabetes-related amputation was significant for body image disturbance. However, it appears that other psychosocial outcomes are better accounted for by medical co-morbidities common in this group rather than the amputation itself. This research certainly highlights that clinicians must assess for and address all potential medical contributors to psychosocial outcomes, rather than assuming that people will experience poorer outcomes following amputation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 25 publications
1
22
0
1
Order By: Relevance
“…The similar and comparable domains, vitality (SF‐36) and energy (NHP), also presented inferior scores for patients with chronic wounds . For emotional‐ and mental health domains, four studies reported lower HRQoL scores for patients with chronic wounds, while five studies did not find any statistical difference when compared to controls . Four studies with control groups reported significantly lower scores for patients with chronic wounds in the domains of bodily pain and pain/discomfort .…”
Section: Resultsmentioning
confidence: 93%
“…The similar and comparable domains, vitality (SF‐36) and energy (NHP), also presented inferior scores for patients with chronic wounds . For emotional‐ and mental health domains, four studies reported lower HRQoL scores for patients with chronic wounds, while five studies did not find any statistical difference when compared to controls . Four studies with control groups reported significantly lower scores for patients with chronic wounds in the domains of bodily pain and pain/discomfort .…”
Section: Resultsmentioning
confidence: 93%
“…Many studies have explored body image disturbance (Senra et al, 2012;Norlyk et al, 2013;McDonald et al, 2014;Norlyk et al, 2016;Khan et al, 2019) and changed self-identify for patients who have undergone major amputations. In the present study, we found that body image and anxiety was a concern for the participants with both major and minor amputation.…”
Section: Social Awareness and Support To Regain Normalitymentioning
confidence: 99%
“…Possibly due to its complications [ 3 , 4 ] and also its effects on activities of daily living and well-being and social life [ 5 9 ], individuals with diabetes are at higher risk of depression [ 10 , 11 ]. The prevalence rate of depression is three-times higher in people with type 1 diabetes and nearly twice as high in people with type 2 diabetes compared to controls [ 12 ].…”
Section: Introductionmentioning
confidence: 99%